2014
DOI: 10.2147/ijn.s55514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titania nanotubes with or without bovine serum albumin loaded on human gingival fibroblasts

Abstract: Modifying the surface of the transmucosal area is a key research area because this process positively affects the three functions of implants: attachment to soft tissue, inhibiting bacterial biofilm adhesion, and the preservation of the crestal bone. To exploit the potential of titania nanotube arrays (TNTs) with or without using bovine serum albumin (BSA) to modify the surface of a dental implant in contact with the transmucosal area, BSA was loaded into TNTs that were fabricated by anodizing Ti sheets; the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 37 publications
(37 reference statements)
6
51
0
Order By: Relevance
“…It is important to emphasize that in these, experiments serum albumin was used as a coating rather than a media supplementation, showing that serum albumin could have other favorable properties besides the above mentioned functions, like molecule transportation. In fact, Liu concluded that adsorbed BSA increased surface energy, roughness and the hydrophilicity of the coated surface, which features promoted the adherence of biological macromolecules and therefore increased the possible connecting points between cells and the material . These results correlate to our present experiment very closely.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is important to emphasize that in these, experiments serum albumin was used as a coating rather than a media supplementation, showing that serum albumin could have other favorable properties besides the above mentioned functions, like molecule transportation. In fact, Liu concluded that adsorbed BSA increased surface energy, roughness and the hydrophilicity of the coated surface, which features promoted the adherence of biological macromolecules and therefore increased the possible connecting points between cells and the material . These results correlate to our present experiment very closely.…”
Section: Discussionsupporting
confidence: 89%
“…In that experiment, the serum albumin coated sutures were able to attach significantly more MSCs after 48 h compared with classical attachment proteins like fibronectin and poly‐ l ‐lysine. More recently, data showed increased early adhesion and faster spreading of human gingival fibroblasts on BSA coated titanium surfaces …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,27,28,30 Considering that the concurrent observation of bone defects and implantation frequently occurred in clinical practice but lacked experiment evidence, this study attempted to develop a wall of bone-defect model of a Ti implant with a TNT-targeting micelle surface in the middle tibia region of normal and ovariectomized rats to probe the biological effects in vivo. Thus, the bone-targeting Ti implant-bone interface in vivo was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 The Ti sheet was mechanically polished and cleaned by sonication in acetone for 30 min, prior to anodization. In a typical procedure, a 2×3 cm 2 , cleaned Ti sheet (99%) with a thickness of 0.1 mm was used as an anode and an iron/tantalum alloy as a cathode.…”
Section: Fabrication and Morphology Of Tnt Arraysmentioning
confidence: 99%